Evaluating a systematic intensive therapy using continuous glucose monitoring and intermittent scanning glucose monitoring in clinical diabetes care: a protocol for a multi-center randomized clinical trial - Ólafsdóttir, Arndís F.; Lind, Marcus (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction: As many persons with type 1 diabetes find it hard to reach the recommended glycemic goals even with CGM, this study analyses whether a closer collaboration with digital support in interpreting CGM-data together with a diabetes nurse can improve glycemic control.Methods & analysis: 120 individuals over 18 years, with HbA1c ≥ 58mmol/mol will be included in the study at 8 different sites in Sweden and Norway. The participants will have to use a CGM or isCGM and be able to upload the data to the appropriate online service for their clinic and sensor. Both those with insulin pumps and insulin pens will be included in the study.Participants will be randomized into two different groups, intensive therapy, and the control group. The intensive therapy group will during the first 4 months upload their glucose data weekly and have telephone contact with their diabetes nurse for support of interpreting CGM-data and make appropriate actions if the mean glucose is above 8.4mmol/l. After the 4 months intensive treatment phase both randomized groups will have the same number of clinical visits and type of diabetes support.Discussion: It is of great importance to find new ways to help persons with type 1 diabetes manage their disease as well as they can, to help them achieve better glycemic control so hopefully more people can achieve the recommended glycemic goals which are associated with fewer diabetes complications. If it is shown that persons with type 1 diabetes achieve better glycemic control with intensive therapy than this can be incorporated in clinical praxis as an option for those not reaching the recommended glycemic goals today.